Hormonal background in young men with epilepsy: the influence of pathology and treatment - Voitiuk, Anna (ScienceRise: Medical Science, 2022)
The study examined the effect of some antiepileptic medications and the disease itself on the hormonal background of young men. The aim of the study was to examine the effect of some antiepileptic drugs and the disease itself on the hormonal background of young men. Methods: This study involved 80 male patients aged 18-44 years. All patients were divided into 4 groups depending on the monotherapy received: carbamazepine (CBZ), valproic acid (VA), levetiracetam (LEV) and oxcarbazepine (OXC). Twenty healthy males aged 18-44 years (31.30 ± 4.07), who met the inclusion criteria, were included in the study as a control group. Venous blood samples (5 mL) were collected in heparinized tubes between 07:00 and 08:00 am after a fasting period of 8 hours for measurement of serum hormones. The levels of estradiol, progesterone, testosterone, and prolactin were determined by chemiluminescence analysis. Results: epilepsy and sexual hormones abnormalities are strictly linked. Moreover, the use of many ASMs (in particular, CBZ, VPA, LEV and OXC) can contribute to these abnormalities in men with epilepsy. Over time, these alterations may result in diminished potency and fertility. Conclusions: the ASMs' therapy may lead to dysregulation of sex hormones and sexual dysfunction in male patients with epilepsy. The use of the liver enzyme inducing AEDs, such as carbamazepine, which increases serum sex hormone binding globulin (SHBG) concentrations. This increase leads to diminished bioactivity of testosterone, which may result in diminished potency and thus reduced fertility. Men taking valproic acid have significantly higher dehydroepiandrosterone levels and lower gonadotropin concentration. This must be considered for the selection of antiepileptic drugs in young male patients. However, the effect of both the disease itself and ASMs’ therapy on hormones in young men requires further research